The ecology of 'we' and ambient warmth: Richard Neutra's ecological architecture. Issue 4 (12th May 2016) - Baek, Jin
Abstract : The article seeks to generate a more nuanced version of environmental ethics than the current positivistic approach taken towards the ecological crisis by referring to the sense of ecology as evident in the practice and writings of Richard Neutra. Despite the whiteness of his architecture, Neutra's architecture was ecological in a profound way in which the ethics of the inter-personal and related dwelling activities of inhabitants are as important as measuring energy performance. For him, more fundamental than man's relationship with nature or natural resources was the inter-personal sharing of 'we', in which scarcity itself is the medium of a proportionate joining. Put differently, the reciprocity between the natural and the inter-personal, in which the former reinforces the latter, was the key to an ecological setting. In the process of underpinning Neutra's sense of the reciprocity between the natural and the inter-personal, as well as the shared inter-personal communication in an atmosphere, this article draws ideas from Japanese intellectual tradition such as Tetsuro Watsuji&s notion of fudo, or climate, and its correlate inter-personal ethics, and Kitaro Nishida's account of a trans-subjective mode of communication of the 'we'. Referring to this Japanese tradition in which Neutra was deeply interested, the article interprets Neutra's architecture based not upon the ego-oriented mode of the 'I' but upon the ego-less mode of ' ek-sistere ' that reinstates the condition of the human being as a pre-reflective corporeal being, or what I would like to call a 'common subjectivity' to be articulated into different, yet conjoined, 'I's to form a joint measure. In this fashion, the article demonstrates how one's relationship with the natural necessarily involves the dimension of the inter-personal, while illuminating the goal of Neutra's practice: securing a place for the inter-personal through the coordination of natural forces.